Local Brain Ischemia Inducing in Rat by Embolic Model of Stroke - Mohammad Allahtavakoli; Rooholah Moloudi; Behnam Heshmatian; Mohammad Reza Rahmani; Mohammad Ebrahim Rezvani (مجله دانشکده پزشکی اصفهان, 2008)
Abstract In patients affected with stroke, most ischemic episodes (80-90%) occur due to occlusion of middle cerebral artery (MCA). Background: Some of blood through femoral artery was withdrawn into a PE- 50 catheter and kept for 2 h in room temperature and 22 h at 4°C to allow old clot formation. Then the catheter was advanced 17 mm in the internal carotid artery until its tip was 1 to 2 mm away from MCA origin. 3-5 µl the preformed clot or 5 µl saline (for sham- operated animals) were injected. Behavioral deficits and seizure activities were recorded at 2, 24, and 48 hours after clot injection. Then the rats were decapitated to remove the brains and prepare them for Tetrazoliume chloride (TTC) staining and analyzing. Methods: When 3 or 5 µl clots were injected, infarct volume was 29.35±1.26% and 16.15±94% respectively (p<0.05). Brain edema also was 8.6±1.65% and 3±1.74%, respectively (p<0.05). There was a significant correlation between infarct volume and brain edema (r=0.56, p<0.05). Behavioral deficit score at 48 hours after clot injection between two groups were significantly different (p<0.05). Findings: This model is very similar to thromboembolic stroke in human and prepares a reliable method for investigating the stroke mechanism. It would also be useful for studying thromboembolic agents' effect on stroke and brain ischemic injury. Conclusion: Brain ischemia, embolic model, brain edema, neurological deficits. Key words: